2018
DOI: 10.1364/ol.43.001982
|View full text |Cite
|
Sign up to set email alerts
|

Observation of soliton molecules in a spatiotemporal mode-locked multimode fiber laser

Abstract: We report on the first experimental observation, to the best of our knowledge, of soliton molecules in a spatiotemporal mode-locked multimode fiber (MMF) laser. By adjusting the waveplates inside the cavity, not only the spatiotemporal mode-locking state with a stable single pulse but also soliton molecules are observed. Various soliton molecules, including soliton pairs, soliton triplets, and soliton quartets with different pulse separations, are achieved. Transition of different operation states with pump po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(71 citation statements)
references
References 22 publications
2
69
0
Order By: Relevance
“…The nonlinear propagation in the MMF lasers is closely related to a complex spatiotemporal mixing process caused by the nonlinearity and waveguide imperfections. 178 Recently, the spatiotemporal dynamics of optical pulses have been demonstrated in the MMFs, such as the spatiotemporal mode-locking, 179 the soliton molecules, 180 harmonic mode locking, 181 the spatiotemporal instability, 182 and beam self-cleaning. 183 This research provides new approaches for exploring RW generation in the MMF lasers.…”
Section: Rogue Waves Based On the Multimode Fiber Or Multimode Fiber mentioning
confidence: 99%
“…The nonlinear propagation in the MMF lasers is closely related to a complex spatiotemporal mixing process caused by the nonlinearity and waveguide imperfections. 178 Recently, the spatiotemporal dynamics of optical pulses have been demonstrated in the MMFs, such as the spatiotemporal mode-locking, 179 the soliton molecules, 180 harmonic mode locking, 181 the spatiotemporal instability, 182 and beam self-cleaning. 183 This research provides new approaches for exploring RW generation in the MMF lasers.…”
Section: Rogue Waves Based On the Multimode Fiber Or Multimode Fiber mentioning
confidence: 99%
“…In addition to the aforementioned studies, spatiotemporal mode-locking was demonstrated with graded-index multimode fibers in multimode fiber laser cavities by Wright et al [21]. Later, observations of the bound state solitons (soliton molecules) and harmonic mode-locking reported in spatiotemporal mode-locked fiber lasers [22,23]. All of these studies presented laser cavities featuring dissipative soliton pulses with Gaussian temporal profile and low output beam quality.…”
mentioning
confidence: 96%
“…3(a-inset)). We observe that spatial filtering is necessary to achieve spatiotemporal mode-locking similarly to dissipative soliton pulses in multimode fiber lasers [21,22]. Beam profiles are measured by a 4f-system with 1.5 magnification.…”
mentioning
confidence: 97%
“…Multimode fibers (MMFs) have found applications in several fields in the last decades mainly in telecommunication and imaging 1,2 . In recent years, spatiotemporal nonlinearities in MMFs, have become the subject of strong interest in various fundamental and applied areas, from single-pass propagation to spatiotemporally mode-locked laser cavities [3][4][5] . In the single-pass nonlinear propagation studies, by using different pulse types from visible to IR wavelengths with a Gaussian beam profile numerous interesting phenomenon [6][7][8][9][10][11][12][13][14][15] including spatiotemporal instability, self-beam cleaning and supercontinuum generation are reported with graded-index multimode fibers (GRIN MMFs).…”
Section: Introductionmentioning
confidence: 99%